Preparação e caracterização de catalisador heterogêneo sintetizado a partir da casca de ovo para produção de biodiesel - Pinto, Rennêr Ribeiro (2021)
The increase in global energy demand, mostly from non-renewable sources, has motivated the development of new sources of alternative energy. In this search for new sources, Biodiesel emerged, a biofuel with low toxicity and biodegradable, generally obtained from the transesterification reaction in which 1 (one) mol of the triacylglycerides reacts with 3 (three) moles of alcohol (methanol or ethanol) to form 3 (three) moles of biodiesel and 1 (one) mole of glycerol, with the help of homogeneous or heterogeneous catalysts. However, the use of heterogeneous catalysts has a higher cost, when compared to homogeneous catalysis, which connotes the search for cheaper raw materials. In order to favor the cost benefit, a study was carried out that consisted of the use of CaO (calcium oxide), which has a high catalytic capacity, obtained from the calcination of the hen's egg shell. Based on this sustainable perspective, this work had as main objective the synthesis and characterization of heterogeneous catalyst obtained from the calcined eggshell, for the production of biodiesel from cottonseed oil and safflower via ethyl route, starting from factorial planning 23. The catalyst was prepared from calcination at different temperatures (600, 700, 800 and 900ºC) for 2 hours, and characterized from X-Ray Diffraction (XRD), Granulometric Distribution (DG), Zeta Potential, Nitrogen Adsorption Analysis (BET/BJH), Experimental Density by Pycnometry (DE) and Infrared Spectroscopy (FTIR). The esters obtained during the transesterification reaction were characterized by gas chromatography and FTIR. In terms of the catalytic activity of CaO, from the applied factorial planning, a maximum yield in the transesterification of 85.83% was obtained for cotton oil, and when the best reaction condition was adopted and the amount of CaO varied from 1 to 5 %, there were excellent conversions of up to 98.76% in biodiesel. Conversions in biodiesel of up to 99.98% were achieved for safflower oil. The results achieved showed a promising application of alternative CaO for the production of biodiesel, making the process even more sustainable.